REFORMULASI MANAJEMEN MUTU BERKELANJUTAN PADA MADRASAH DALAM MENINGKATKAN DAYA SAING LULUSAN DI ERA TRANSFORMASI PENDIDIKAN NASIONAL - Nasrun; Saifudin; Sri Fatmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of national education education, marked by the digitalization of learning, the implementation of the Independent Curriculum, and the strengthening of 21st century competencies, requires madrasahs to adapt and sustainably reform their governance systems. Madrasahs, as Islamic educational institutions under the auspices of the Ministry of Religious Affairs of the Republic of Indonesia, face the challenge of enhancing the competitiveness of graduates without abandoning their Islamic identity. This article aims to analyze the urgency and strategies for sustainable quality management reformulation to enhance the competitiveness of madrasah graduates in the era of national education transformation. This research uses a qualitative approach with library research through analysis of relevant literature related to educational quality management, transformational leadership, and education policy. The study results indicate that quality management reformulation needs to be directed at strengthening a quality culture, optimizing a data-based quality assurance system, developing teacher professionalism, and integrating Islamic values with 21st-century competencies. With systematic and sustainable reformulation, madrasahs can produce graduates who excel academically and religiously, adapt to technological developments, and are competitive in continuing their studies and entering the workforce.